Special Features in The Interpretation of Babur’s Personality - Khayrullayeva Kamola Ravshanovna (Zien Journals, 2022)
This article researches on interpretation of Zahiriddin Muhammad Babur's personality in English, Indian and Uzbek literature. During the researches literary works by authors of these nations are widely analyzed. Description of Babur’s personality as a son and brother, husband and father are displayed in a comparative way. Parts of the literary works are included where we can identify personal features of Zahiriddin Muhammad Babur.
Keywords: Zahiriddin Muhammad Babur; turks; mongols; son